(3GdbUjOI GdZhKjIs - (3eMeO Hf fGUQs
(3ChdgG (B:s
(3GdMeO ddg GdPj HCeQg (B*** (3jHdZ PRh GdbUO JeGe bUOg , jG ef Edi QMeJg GdeaQ (B*** (3hef Edjg jdLC GdeVWQ , hjG bQjH GdYah jG ehdGg (B*** (3hjG eZjK cd ef OYGgs
(3BNQgG (B:s
(3UdGJc GdJj Jbj HCeQg (B*** (3ceG jdjb HGQJaGY bOQg , Ke Ydi GdCgd GdcQGe hYdi (B*** (3CUMGHg GdZQ hef dge JdG , hGdMeO ddg GdPj HCeQg (B*** (3jHdZ Ph GdbUO JeGe bUOgs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs